Teaching Technique Support System Based on Classroom Indoor Air Quality (IAQ) Analysis - Nazira, Azman; Sarah Nabiha, Hamdan; Nor Azhar, Ahmad (Faculty of Computer Systems & Software Engineering, Universiti Malaysia Pahang, 2016)
This project is about to help the teacher to identify their student performance inside the school classroom. The system will tell the teacher about student performance or condition. It will help the teacher to take an action to prevent their student learning in the low performance. This system is beneficial to the teacher. To develop this system, we need to use sensors to detect the present of carbon monoxide, carbon dioxide, dust, and mold. With the presence of all particle and gas, it will give bad impact toward the indoor air quality (IAQ) inside the school classroom. It will affect student performance. The system will calculate the rate of particle and gas and compare with the standard of indoor air quality that have been set by the Department of Occupational Safety and Health (DOSH). With using production rules, this system will manipulate knowledge to interpret student condition. The constraints that have been faced are problems to take the reading of indoor air quality and limited time. This system can be tested in the classroom at the school. The future development of this project is system can automatically fixing the problem of indoor air quality. An example as followed : when the carbon dioxide in the classroom is high, another system provides oxygen automatically.